The bilingual child : his adjustment difficulties and second language attainments - Rama Rao, T. S. (Tirukampuliyar Srinivasarao), 1928- (Indian International Publications, 1975)
Study of bilingualism in a sampling of Indian school children in Tamil Nadu.